Evaluation of the Marginal Adaptation of ProRoot MTA, Biodentine, and RetroMTA as Root-end Filling Materials - Marjan Bolbolian; Farnaz Seyed Mostafaei; Seyedmatin Faegh (Wolters Kluwer Medknow Publications, 2020)
Introduction: Evaluation of the marginal adaptation of root-end filling materials to root canal walls provides invaluable information on their sealing ability. Different materials, such as Mineral Trioxide Aggregate (MTA), have been used for root-end fillings. Recently, elements such as RetroMTA or Biodentine have been introduced to overcome the drawbacks of MTA. This research was carried out to evaluate the marginal adaptation of root-end filling materials, RetroMTA, Biodentine, and ProRoot MTA, using an experimental method. Materials and Methods: In this experimental research, 45 single-rooted teeth were prepared and obturated; then, 3 mm of the apical third of the roots were resected, and root-end cavities were prepared using a standard ultrasonic method. The teeth were randomly divided into three groups and filled with RetroMTA, Biodentine, and ProRoot MTA. After a week, epoxy resin replicas of the root-ended surfaces were provided after a longitudinal section. The size of gaps between the filling material and the canal walls were measured with SEM at longitudinal and transverse sections at eight points and compared between the three filling materials using one-way ANOVA. Results: The mean gaps between the filling material and canal wall in Biodentine, Retro-MTA, and MTA ProRoot groups in longitudinal sections were rated at 4.49 µm, 8.55 µm, and 14.34 µm, respectively (P = 0.007). However, no significant differences were identified between the three filling materials in transverse sections. Conclusion: The best marginal adaption in longitudinal sections were identified in Biodentine, RetroMTA, and MTA ProRoot, respectively. However, in transverse sections, there were no significant differences between the three materials.